Inquiry and Change Work for Equitable Post-Graduation Success: Customized Labor Market Data as a Leadership Tool - Robert Johnstone (Educational Considerations, 2025)
This article explores utilizing a post-graduation success lens to help community college leaders frame the challenges of achieving equitable improvement for their students. Specifically, it posits that providing and exploring customized labor market data presented in an accessible format can help institutional leaders provide a “true north” to college change efforts and serve as a departure point for future highly impactful change work. The article makes the case for exploring post-graduation success data as critical for community college leaders and their teams; briefly introduces available tools to engage in such exploration; provides three key data exploration illustrations using real labor market data; and, explores potential avenues for addressing challenges illuminated by the post-graduation success data.
Keywords: Institutional Change; Equity; Post-Graduation Success; Labor Market Data; Living Wage Attainment